Household poverty, schooling, stigma and quality of life in adolescents with epilepsy in rural Uganda - Anguzu, R; Akun, P; Katairo, T; Abbo, C; Ningwa, A; Ogwang, R; Mwaka, AD; Marsh, K; Newton, CR; Idro, R (Elsevier, 2020)
Background: Epilepsy remains a leading chronic neurological disorder in Low- and Middle-Income Countries. In Uganda, the highest burden is among young rural people. We aimed to; (i) describe socio-economic status (including schooling), and household poverty in adolescents living with epilepsy (ALE) compared to unaffected counterparts in the same communities and (ii) determine the factors associated with the overall quality of life (QoL).